PENGARUH GAYA KEPEMIMPINAN, MANAJEMEN PENGETAHUAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA KANTOR WILAYAH HUKUM DAN HAM PROVINSI SULAWESI TENGGARA - Asriani Asriani; Dedy Takdir Syaifuddin; La Ode Kalimin (Pascasarjana Universitas Halu Oleo, 2020)
This study aims to determine and analyze: (1) The influence of leadership style on employee performance at the Regional Office of the Ministry of Law and Human Rights (Kemenkumham) Southeast Sulawesi Province, (2) The influence of knowledge management on employee performance at the Regional Office of the Ministry of Law and Human Rights (Kemenkumham) Southeast Sulawesi Province, and (3) The influence of organizational commitment on employee performance at the Regional Office of the Ministry of Law and Human Rights (Kemenkumham) Southeast Sulawesi Province. The population in this study were all Civil Servants at the Regional Office of the Ministry of Law and Human Rights (Kemenkumham) Southeast Sulawesi Province, totaling 113 employees. Withdrawal of samples by census method so that sampling is not required The analysis technique used is Partial Least Square (PLS), with the calculation process using SmartPLS software.The results showed that: (1) Leadership style has a positive and significant effect on employee performance at the Regional Office of the Ministry of Law and Human Rights of Southeast Sulawesi Province, (2) Knowledge management has a positive and significant effect on employee performance at the Regional Office of the Ministry of Law and Ham, Southeast Sulawesi Province, (3) Organizational commitment has a positive and significant effect on employee performance at the Regional Office of the Ministry of Law and Human Rights, Southeast Sulawesi Province.